DETERMINATION OF PROCESS PARAMETER FOR INJECTION MOLDING : A REVIEW - Arifin, Muhammad Alfattah; Pranoto, Hadi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
One of the most suitable methods for mass production of complicated shapes is injection molding due to its superior production speed and quality. Plastic injection is the process of forming products from plastic materials with variations in shape and size. Controlling the quality of plastic products is an important aspect of the plastic injection molding process. To achieve high process effectiveness and desired product quality, correct and precise parameter settings are essential. One of the benchmarks for assessing the productivity and efficiency of an industry is to look at the level of product defects that occur in producing a product. This article aims to provide a brief review of the explanation of injection molding, types of molding, types of injection failure, experimental methods in determining injection molding parameters. Types of failure in the injection process such as short shot, weld mark, warpage, sink mark, air trap, black spot, flashing, hole, over molding, delamination. The experimental method determines parameters such as the Taguchi method, ANOVA method, hard computing techniques. The future will likely tend to use AI techniques as has happened with other methods in manufacturing processes to complement conventional techniques in determining injection molding process parameters.